The Nexus between R&D, Financial Development and Sustainable Development - Ivan Sudibyo; Tasya Ayu Noorhaliza (Westscience Press, 2026)
The present study examines the connection among financial development, research and development expenditure and carbon dioxide emissions across seven Asian nations namely Japan, Korea, Singapore, Indonesia, Malaysia, Thailand and Vietnam. The author examined the years 1996–2021 using information from Global Financial Development and the World Bank Development Indicator. The author's research shows that R&D spending and financial development lower CO2 emissions in both developed and developing nations. Each country has a variety of estimation results. Furthermore, policies relating to sustainable development are discussed.